Alat Terapi Gerak Jari Tangan untuk Pasien dengan Cedera Plexus Brachialis - Lanny Agustine; Oscar Setiawan; Andrew Joewono (Sanata Dharma University, 2016)
People with damaged or injured plexus brachialisneed immediate therapy after the surgery, as an effort to restore the nerves function, even thou it is hard to achieve. But, continuous treatment may prevent the muscle to become stiff and shrink. So, patient needs assistive device to be used at home for regular self therapy.Physical therapy method was chose to be developed in this research because of lower risk than electrical therapy. This assistive device is designed in two modes, manual and automatic, and it is limited to fingers movement of adults right hand. Manual mode is focusing to 1 finger movement, while automatic mode will move the five fingers consecutively. The movement procedure is imitated those given in the clinic, by controlling the speed and angle rotation of a dc servo motor and certain design of lever for each finger.This assistive device works effectively for a certain fingers size. It takes 5.29 sec to finish one cycle in automatic mode, and about 2 sec in manual mode. The degree of finger movement yield by the device is about 20 degree less than finger maximum ROM for MCP and PIP joint of index finger, pinky, and thumb.